LncRNATUG1 Facilitates Th2 Cell Differentiation by Targeting the miR-29c/B7-H3 Axis on Macrophages - Sun, Huiming; Wang, Ting; Zhang, Weili; Dong, Heting; Gu, Wenjing; Huang, Li; Yan, Yongdong; Zhu, Canhong; Chen, Zhengrong (Frontiers in Immunology, 2021)
The role of long non-coding RNAs (lncRNA) in asthma remains unclear. In this study, we examined the role of long non-coding RNA taurine upregulated 1 (lncRNA TUG1) in asthma. We found that lncRNA TUG1 is one of the differentially expressed lncRNAs in monocytes of asthmatic children and is associated with Th cell differentiation. LncRNA TUG1 and miR-29c are mainly distributed in the cytoplasm of macrophages. Our data suggested that lncRNA TUG1 increased in macrophages stimulated by House Dust Mite in a dose-dependent manner. Using loss- and gain of function strategy, we found that miR-29c might regulate Th2 cell differentiation by directly targeting co-stimulatory molecule B7-H3. Furthermore, down-regulation of lncRNA TUG1 decreased the level of GATA3 in CD4+T cells and was associated with miR-29c/B7-H3 axis. Moreover, the dual-luciferase reporter assay confirmed that lncRNA TUG1 serves as a competing endogenous RNA to sponge miR-29c. According to the rescue experiment, lncRNA TUG1 regulated Th2 cell differentiation via miR-29c. To sum up, these data suggest that lncRNA TUG1 in macrophages regulates Th2 cell differentiation via miR-29c/B7-H3 axis.